Diseño de una propuesta mercadológica basada en los conceptos de responsabilidad social empresarial para la empresa Mavesa – línea John Deere, dedicada a la prestación de servicios y comercialización de maquinaria pesada de la ciudad de Quito. - Aragón Toazo, Verónica Alexandra (2015)
Machinery and Vehicles Inc. is legally company established in Ecuador since 1936. With extensive experience in the market, Mavesa Group has demonstrated to be one of the most prestigious in the automotive field through its five product line companies: Hino, Bridgestone, Citroen, Marangoni and John Deere. In the year 2012 in order to contribute to the progress of the industrial development of the country, Mavesa Group introduced to market John Deere construction machinery, which so far has had great success in its manufacturing sector. Being one of the recently lines integrated to the group, the company had contemplate the possibility to direct its activities towards the well-being of society in general; such result will translate also in benefit of the company due to the global trend towards sustainable development that exists today. In an effort to enhance the positioning of the brand and reflecting the guideline of sustainable development, we have considered a range of focused Social Responsibility strategies. In the first instance, allowing the Mavesa Machinery Group line to increase marketing, and thus expand their universe of sales in the future to socialize these strategies and cover all the production lines of the group. From the implementation of the strategies suggested in this analysis, the image of Machinery and Vehicles S.A will be affected positively, achieving sustainable pace and sustainable growth of the brand.